Viral Vector Vaccines Against ASF: Problems and Prospectives - Ravilov, Rustam Kh.; Rizvanov, Albert A.; Mingaleev, Danil N.; Galeeva, Antonina G.; Zakirova, Elena Yu.; Shuralev, Eduard A.; Rutland, Catrin S.; Khammadov, Nail I.; Efimova, Marina A. (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is a highly contagious viral disease affecting pigs, with mortality rates a primary focus as they can reach up to 100%. The widespread and colossal economic losses from ASF have impacts on the development of animal husbandry practices in most countries within Africa, Asia, and Europe. Currently, a variety of approaches toward the development of vaccines against ASF are being employed. A promising new concept centered around more economical and time-consuming vaccine production is based on the use of viral vectors to deliver selected immunogens. This review discusses the results obtained from testing various viral vectors as carriers of targeted ASF virus genes. The safety and prospects of viral vectors, the possibilities around modulating cellular and humoral immune responses by choosing genes expressing immunodominant antigens, and the degree of protection in experimental animals from infection with a lethal dose of virulent ASF virus strains have been shown and discussed.